Leadership of School Administrators Towards Effective Implementation of the Akita Model. - Chotipiboonsub, Jareeporn (Academic and Research Journal of Liberal Arts (Online), 2022)
This article aims to present the leadership concepts of school administrators in implementing the Akita Model effectively, which are: 1) Have a vision and knowledge of the Akita Model to be conveyed to the team in detail and correctly in terms of philosophy, concepts, principles, nature of learners, teaching methods and processes measurement and evaluation and good practices from educational institutions that have performed effective; 2) Induce and create a positive attitude towards teaching the Akita Model to teachers to adjust the role of students as learning leaders, set clear goals, stimulate and motivate learners to have fun and have their own ideas; 3) Build an effective team of teachers by encouraging them to collaborate in teaching in one style and direction; 4) Educating and practicing Akita Model teaching skills for teachers to understand participatory learning management for both teachers. family and community; 5) Understanding parents and communities, create interactions, convey and disseminate principles, concepts, and active teaching approaches. to see that the school belongs to the commons of parents and the community; 6) Create a system to promote and motivate the teaching team by setting a policy. packaged in plans have a clear goal allocate supporting resources, designate active teaching management as a measure of operator success and part of performance evaluation; 7) Driving active teaching and continuous development; And 8) Create an open atmosphere, build morale and morale for the teaching team, provide care, give advice, give appreciation and encouragement, organize learning exchange activities and reward.